Diversity and Distribution of Phytophthora Species Along an Elevation Gradient in Natural and Semi-Natural Forest Ecosystems in Portugal - Carlo Bregant; Eduardo Batista; Sandra Hilário; Benedetto Teodoro Linaldeddu; Artur Alves (Pathogens)
Globally, forests are constantly threatened by a plethora of disturbances of natural and anthropogenic origin, such as climate change, forest fires, urbanization, and pollution. Besides the most common stressors, during the last few years, Portuguese forests have been impacted by severe decline phenomena caused by invasive pathogens, many of which belong to the genus Phytophthora. The genus Phytophthora includes a large number of species that are invading forest ecosystems worldwide, chiefly as a consequence of global trade and human activities. This paper reports the results of a survey of Phytophthora diversity in natural and semi-natural forest ecosystems in Portugal along an elevation gradient. Isolations performed from 138 symptomatic plant tissues and rhizosphere samples collected from 26 plant species yielded a total of 19 Phytophthora species belonging to 6 phylogenetic clades, including P. cinnamomi (36 isolates), P. multivora (20), P. plurivora (9), P. cactorum (8), P. lacustris (8), P. pseudocryptogea (8), P. amnicola (6), P. hedraiandra (6), P. pseudosyringae (5), P. thermophila (5), P. bilorbang (4), P. inundata (4), P. asparagi (3), P. citricola (3), P. gonapodyides (3), P. rosacearum (3), P. chlamydospora (2), P. pachypleura (2), and P. syringae (1). Overall, the data obtained highlight the widespread occurrence of P. cinnamomi in natural ecosystems from sea level to mountain habitats. The results of the pathogenicity tests carried out on 2-year-old chestnut plants confirmed the key role of P. cinnamomi in the recrudescence of chestnut ink disease and the additional risk posed by P. pachypleura, P. plurivora, and P. multivora to Portuguese chestnut forests. Finally, three species, P. citricola, P. hedraiandra, and P. pachypleura, are reported for the first time in the natural ecosystems of Portugal.